Sleep Disorder: An Overlooked Manifestation of Glucose Transporter Type-1 Deficiency Syndrome - Anurat, Kingthong; Khongkhatithum, Chaiyos; Tim-Aroon, Thipwimol; Limwongse, Chanin; Thampratankul, Lunliya (Neuropediatrics, 2021)
Glucose transporter type-1 deficiency syndrome (Glut1 DS) is a rare disorder with various manifestations. Early diagnosis is crucial because treatment with the ketogenic diet can lead to clinical improvement. Here, we report the cases of two siblings with Glut1 DS and one of them presented with sleep disorder which is a rare and atypical manifestation of Glut1 DS. Patient 1 was a 3.5-year-old boy who presented with paroxysmal loss of tone and weakness of the whole body with unresponsiveness after waking up. He also had excessive daytime sleepiness, insomnia, and restless sleep. His other clinical findings included focal seizures, paroxysmal exercise-induced dyskinesia (PED), ataxia, mild global developmental delay, and hyperactivity. Patient 2 was a 5.5-year-old boy who presented with drug-resistant focal epilepsy, global developmental delay, paroxysmal dystonia, and ataxia. A novel heterozygous nonsense variant of SLC2A1, c.1177G > T (p.Glu393*), classified as a pathogenic variant, was identified in both patients, but not in their parents' blood. After treatment with the modified Atkins diet, their neurological functions significantly improved. In conclusion, we reported two siblings with variable phenotypes of Glut1 DS with a novel nonsense mutation. Although sleep disorder and daytime somnolence were the nonclassical manifestations of Glut1 DS, the diagnostic evaluation of possible Glut1 DS in patients presented with daytime sleepiness, particularly in cases with the cooccurrence of seizures or movement disorders should be considered.
Keywords: glucose transporter type-1 deficiency syndrome; familial Glut1 DS; sleep disorder; daytime somnolence; seizure; paroxysmal exercise-induced dyskinesia